The Italian telephone-based Verbal Fluency Battery (t-VFB): standardization and preliminary clinical usability evidence - Aiello, Edoardo Nicolò; Preti, Alice Naomi; Pucci, Veronica; Diana, Lorenzo; Corvaglia, Alessia; Barattieri di San Pietro, Chiara; Difonzo, Teresa; Zago, Stefano; Appollonio, Ildebrando; Mondini, Sara; Bolognini, Nadia (Frontiers in Psychology, 2022)
Background This study aimed at standardizing and providing preliminary evidence on the clinical usability of the Italian telephone-based Verbal Fluency Battery (t-VFB), which includes phonemic (t-PVF), semantic (t-SVF) and alternate (t-AVF) verbal fluency tasks. Methods Three-hundred and thirty-five Italian healthy participants (HPs; 140 males; age range = 18–96 years; education range = 4–23 years) and 27 individuals with neurodegenerative or cerebrovascular diseases were administered the t-VFB. Switch number and cluster size were computed via latent semantic analyses. HPs underwent the telephone-based Mental State Examination (MMSE) and Backward Digit Span (BDS). Construct validity, factorial structure, internal consistency, test-retest and inter-rater reliability and equivalence with the in-person Verbal Fluency tasks were assessed. Norms were derived via Equivalent Scores. Diagnostic accuracy against clinical populations was assessed. Results The majority of t-VFB scores correlated among each other and with the BDS, but not with the MMSE. Switch number correlated with t-PVF, t-SVF, t-AVF scores, whilst cluster size with the t-SVF and t-AVF scores only. The t-VFB was underpinned by a mono-component structure and was internally consistent (Cronbach’s α = 0.91). Test-retest (ICC = 0.69–0.95) and inter-rater reliability (ICC = 0.98–1) were optimal. Each t-VFB test was statistically equivalent to its in-person version (equivalence bounds yielding a p < 0.05). Education predicted all t-VFB scores, whereas age t-SVF and t-AVF scores and sex only some t-SVF scores. Diagnostic accuracy against clinical samples was optimal (AUC = 0.81–0.86). Discussion The t-VFB is a valid, reliable and normed telephone-based assessment tool for language and executive functioning, equivalent to the in-person version; results show promising evidence of its diagnostic accuracy in neurological populations.